2016
DOI: 10.3389/fphar.2016.00496
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive Effects of AGAP, a Recombinant Neurotoxic Polypeptide: Possible Involvement of the Tetrodotoxin-Resistant Sodium Channels in Small Dorsal Root Ganglia Neurons

Abstract: Antitumor-analgesic peptide (AGAP) is a novel recombinant polypeptide. The primary study showed that AGAP 1.0 mg/kg exhibited strong analgesic and antitumor effects. The tail vein administration of AGAP potently reduced pain behaviors in mice induced by intraplantar injection of formalin or intraperitoneal injection of acetic acid, without affecting basal pain perception. To further assess the mechanisms of AGAP, the effects of AGAP on sodium channels were assessed using the whole-cell patch clamp recordings i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…Animal studies have demonstrated that the scorpion venom peptide BmK AGAP exhibit strong analgesic activity with minimum advert effects compared with morphine [4,5,6]. However, it is not clear the mechanisms of the BmK AGAP analgesic activities, as well as the structure-function relationship of voltage-gated sodium channels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Animal studies have demonstrated that the scorpion venom peptide BmK AGAP exhibit strong analgesic activity with minimum advert effects compared with morphine [4,5,6]. However, it is not clear the mechanisms of the BmK AGAP analgesic activities, as well as the structure-function relationship of voltage-gated sodium channels.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that it is a sodium channel-specific neurotoxin. It blocks neuron transmission by binding to voltage-independently at site-3 of sodium channels and inactivate the activated sodium channels to elicit potent analgesic activity [4,5]. Local anesthetics such as lidocaine is indicated to mediate the analgesic activities of Nav 1.3, Nav 1.7, Nav 1.8, and Nav 1.9 subunits by non-selectively blocking the voltage-gated sodium channels [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Voltage-gated sodium channels (VGSCs) facilitate the internal sodium current in the brain and peripheral nerves [ 16 ]. VGSCs are thus crucial in triggering as well as propagation of action potentials in excitable tissues such as the brain and peripheral nerves [ 17 ].…”
Section: Bmk Agap and Voltage-gated Channelsmentioning
confidence: 99%